(3QSGdI eYQGL fLGg GdehMOjf hSde MjGI Gdehbfjfs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi Gdehdi GdMGce GdefRg Yf GdEOQGc hGdYOe hTcQJ YHOg GdbGFe EeGe GdCFeI hhdi GdfYe hGdcHQjGA CeG HYO aEf GdhGLH Ydi GdeQA GdYGbd s
(3BNQgG (B:s
(3hEPG HdZ GdYHO GdfGUM ajeG Cedg hfhGg GdZQV JeJ GdQSGdI hef hdi GdMb fQLhG GdYah hGdeZaQI hGdEbGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B68s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds